2022
DOI: 10.1186/s40594-022-00377-5
|View full text |Cite
|
Sign up to set email alerts
|

The application of AI technologies in STEM education: a systematic review from 2011 to 2021

Abstract: Background The application of artificial intelligence (AI) in STEM education (AI-STEM), as an emerging field, is confronted with a challenge of integrating diverse AI techniques and complex educational elements to meet instructional and learning needs. To gain a comprehensive understanding of AI applications in STEM education, this study conducted a systematic review to examine 63 empirical AI-STEM research from 2011 to 2021, grounded upon a general system theory (GST) framework. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 108 publications
1
25
0
1
Order By: Relevance
“…The years with the highest scholarly production (Figure 2) were 2013, 2019, and 2020. The most frequently used keywords were found to be (Table 2): Augmented reality (59), Students (34), Education (26), Computer-aided instruction (21), Teaching ( 21), Elearning (17), Engineering education (15), Virtual reality (14), Interactive learning environment (12) and, Learning systems (11). Concerning the keywords used by the authors (Figure 4), a total of 211 were found in the sample, of which 36 had appeared at least twice, with the most frequent being: Augmented Reality (39), Interactive learning environments (12), Virtual Reality (9), Education (8), Applications in subjects' areas (6) and Mobile learning (6).…”
Section: Resultsmentioning
confidence: 99%
“…The years with the highest scholarly production (Figure 2) were 2013, 2019, and 2020. The most frequently used keywords were found to be (Table 2): Augmented reality (59), Students (34), Education (26), Computer-aided instruction (21), Teaching ( 21), Elearning (17), Engineering education (15), Virtual reality (14), Interactive learning environment (12) and, Learning systems (11). Concerning the keywords used by the authors (Figure 4), a total of 211 were found in the sample, of which 36 had appeared at least twice, with the most frequent being: Augmented Reality (39), Interactive learning environments (12), Virtual Reality (9), Education (8), Applications in subjects' areas (6) and Mobile learning (6).…”
Section: Resultsmentioning
confidence: 99%
“…With the call to increase assessments using open-ended tasks, several researchers have turned toward artificial intelligence (AI) and machine learning (ML) approaches to automatically analyze student responses. One use for ML classification is to provide automated, tailored, formative feedback to students . However, advanced ML technologiessimilar to those which enable the classification of student responses to complex, open-ended writing taskscan also be used for another ML task: natural language generation .…”
Section: Introductionmentioning
confidence: 99%
“…One of the applications of automated evaluation with ML are adaptive interventions and automated feedback for student responses to open-ended tasks . For example, students could be provided with adaptive tutorials for specific concepts based on the automated score they receive for a related constructed response item. , Additionally, research demonstrates the translation of ML models to develop an automated, formative feedback tool for the organic chemistry WTL assignments specifically .…”
Section: Introductionmentioning
confidence: 99%
“…The application of Artificial Intelligence (AI) has upgraded different aspects of our lives. The banking [1], healthcare [2], education [3], agriculture [4], industrial automation [5], transportation [6], and many different sectors are leveraging the AI technology to reduce human intervention and automating services. The application of AI in cybersecurity and its effectiveness is worth attention as well [7].…”
Section: Introductionmentioning
confidence: 99%